Meanings of organization and community participation in vulnerable communities in Metropolitan Lima - Cueto, Rosa María (2015)
The study analyzes the speech of people from marginal urban areas of Lima for the meanings and their assessment of organizational processes and participation in their localities. Twenty two in-depth interviews were conducted in 3 settlements in the southern cone of Lima. The results show that family and community networks are valued as resources that can face the challenges of living in an environment perceived as precarious. The organization and community participation are important strategies to overcome their difficulties. Interviewees identify a number of weaknesses in the strategies, like the lack of recent positive experiences and the wear from over-use of these local resources to answer collective problems.